Early impact of the PEN HEARTS package to manage noncommunicable diseases in Bhutan: a mixed-methods evaluation - Karma Tenzin; Lora Sabin; Wangchuk; Karma Choden; Frank Feeley; Sangay Zam; Nafisa Halim; Bolanle Banigbe; Zimba Letho; Emily George; Kinzang Yangden; Jennifer Beard; et al. (James Cook University, 2022)
Introduction: Non-communicable diseases (NCDs) pose significant public health challenges in Bhutan. In 2019, Bhutan's Ministry of Health introduced a set of interventions associated with the World Health Organization's Package of Essential Noncommunicable Disease Interventions for Primary Health Care in Low-Income Settings called PEN HEARTS. This initiative encompassed six components: healthy lifestyle intervention, evidence-based protocols, access to medicines and technology, risk-based management, team-based care, and systems monitoring. Evaluations of PEN interventions in other countries documented barriers to implementation. The present report provides the result of a 2019-2020 evaluation assessing implementation of PEN HEARTS in Bhutan and initial impacts on provision of care for NCDs and patient outcomes. Methods: A cross-sectional, mixed-methods evaluation was conducted in six districts, two where the interventions were first initiated, two where they were implemented subsequently, and two where no implementation had begun. In each district, data were collected at the district hospital and three basic health units. Quantitative data collection encompassed facility checklists, health worker surveys, and patient record abstraction. For the survey, health workers were selected using random or convenience sampling depending on facility size. For patient record abstraction, enumerators created a sampling frame at each facility to include eligible patients who were then selected randomly for record review. Qualitative data collection included in-depth interviews (IDIs) with health workers, and IDIs with NCD patients. A convenience sample of health worker IDI participants was selected randomly at hospitals; all health workers at BHUs were invited to participate. A convenience sample of NCD patients was recruited from facility waiting rooms on the day(s) of data collection. Lastly, a convenience sample of homebound patients was recruited to participate in IDIs. Quantitative analysis methods included bivariate analysis of categorical and continuous variables, and pairwise comparisons among groups. Qualitative data were analyzed using thematic content analysis with inductive coding. Results: A total of 153 health workers participated in the knowledge survey and 121 patient records were reviewed. IDIs were conducted with 13 health workers, 18 hospital or BHU patients, and four homebound patients. Most elements of the PEN HEARTS program were implemented as planned, including monitoring and supervision. PEN HEARTS had a positive impact on disease control: group A districts had a significantly lower proportion of patients with a treatment gap (p<0.001) and a significantly higher proportion of patients retained in care (p<0.001). Health workers experienced implementation challenges in four main areas: human resources, medicine shortages, equipment failure, and record-keeping. They also described benefits from increased supervision and peer support. Patients described experiencing more patient-centered care and overall positive experiences with the program. Conclusion: The evaluation identified areas of PEN HEARTS implementation that should be strengthened and improved, particularly training, record-keeping, and the use of AUDIT and cardiovascular disease risk assessments. The evaluation also showed evidence of improved disease control across achievement of treatment goals, reduction of treatment gaps, and improved patient retention in care. PEN HEARTS has potential to make a difference for NCD patients, and focusing on improving future implementation may further yield benefits in Bhutan.